Influence of dietary (n-3)-polyunsaturated fatty acids on leukotriene B4 and prostaglandin E2 synthesis and course of experimental tuberculosis in guinea pigs - Mayatepek, Ertan; Paul, Karl; Leichsenring, Michael; Pfisterer, Mathias Hans-Dieter; Wagner, D.; Domann, M.; Bremer, Hans J.; Sonntag, Hans-Günther (Infection, 1994)
In the present study eicosanoid synthesis was studied in macrophages of guinea pigs fed different amounts of (n-6)- and (n-3)-polyunsaturated fatty acids (PUFA). Three groups of weanling guinea pigs were fed by isocaloric diets differing only in their contents of PUFA: controls with 2.8 Cal% of linoleic acid (LA; 18:2(n-6)); (n-6)-rich fed animals with 15.4 Cal% of LA; and (n-3)-rich fed animals with 10.1 Cal% of LA, 1.4 Cal% of eicosapentaenoic acid (20:5(n-3)) and docosahexaenoic acid (22:6(n-3)). After 13 weeks half the number of animals from each group was infected i.m. by 180 colony forming units ofMycobacterium tuberculosis strain H37Rv. Seven weeks after infection the release of leukotriene (LT)B4 and prostaglandin (PG)E2 was quantified in calcium ionophore stimulated whole blood, peritoneal macrophage cultures and alveolar macrophages by immunoassays after high performance liquid chromatography. Synthesis of LTB4 and PGE2 was found to be reduced in (n-3)-rich fed guinea pigs (p<0.05), and equivalent between controls and (n-6)-rich fed animals. Controls and (n-6)-rich fed animals showed the same mycobacterial counts in the spleen whereas (n-3)-rich fed guinea pigs demonstrated an increased number of mycobacteria (p<0.05). Our results demonstrate that an increased dietary intake of (n-3)-PUFA suppress LTB4 and PGE2 synthesis. The increased number ofM. tuberculosis found in the spleens of (n-3)-rich fed animals could represent persistence of the experimental infection. It may be speculated that a functional relationship exists between the two findings.